Quantitative analysis of Anaplasma marginale acquisition and transmission by Dermacentor andersoni fed in vitro - Vimonish, Rubikah (Sci Rep, 2020)
In this study, we describe a new in vitro tick feeding system that facilitates the study of ticks and tick-borne pathogens. To optimize the system, we used Dermacentor andersoni and Anaplasma marginale as a tick-pathogen interaction model. Ticks were fed on bovine blood containing 10-fold dilutions of the pathogen to determine the effect of dose on tick infection rate. After feeding on infected blood, ticks were transferred to uninfected blood to stimulate bacterial replication within the tick vector. During stimulation feeding, blood samples were collected daily to determine if infected ticks secreted viable A. marginale. The results demonstrated similar attachment rates between the first and second tick feeding. Tick midgut and salivary glands were infected with A. marginale. However, salivary gland infection rates decreased as the percentage of parasitized erythrocytes decreased during tick acquisition feeding. Bacteria recovered from the in vitro system were able to infect a naïve bovine host. Using the highly transmissible A. marginale St. Maries strain, we demonstrated that the artificial tick feeding system is a suitable tool to study tick-pathogen interactions and that A. marginale tick salivary gland infection is dose dependent. This work demonstrates the utility of an artificial tick feeding system to directly study the association between the number of acquired pathogens and transmissibility by ticks.